2021
DOI: 10.1007/s40979-021-00082-w
|View full text |Cite
|
Sign up to set email alerts
|

Some students plagiarism tricks, and tips for effective check

Abstract: One of the main goals of assignments in the academic environment is to assess the students’ knowledge and mastery of a specific topic, and it is crucial to ensure that the work is original and has been solely made by the students to assess their competence acquisition. Therefore, Text-Matching Software Products (TMSPs) are used by academic institutes to ensure academic integrity and address plagiarism. However, some students find ways to trick TMSPS. In this paper, files with the common tricks students do to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Detection vendors and application owners claim detection rates of often 80 percent to more than 90 percent accuracy. Several independent studies of often the very same applications find rates to be 20 percent to 50 percent or even lower (Elkhatat et al, 2023; Hines, 2023; Weber-Wulff et al, 2023). The authors often concluded that detector sensitivity/specificity may limit their effectiveness in identifying AI-generated text.…”
Section: Accuracy and Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection vendors and application owners claim detection rates of often 80 percent to more than 90 percent accuracy. Several independent studies of often the very same applications find rates to be 20 percent to 50 percent or even lower (Elkhatat et al, 2023; Hines, 2023; Weber-Wulff et al, 2023). The authors often concluded that detector sensitivity/specificity may limit their effectiveness in identifying AI-generated text.…”
Section: Accuracy and Biasmentioning
confidence: 99%
“…The line is blurred as to when using generative AI for brainstorming, summarization, or revision crosses over into plagiarism and academic misconduct. To add to the complexity, detectors do not test findings in a consistent way (Elkhatat et al, 2023), with some using measures like likelihood of AI generation versus percentage of content that was AI generated. Students and educators are left confused and lacking in direction as to when and how much generative AI is allowed, a compounding stressor for those still nursing their COVID-19 academic hangover.…”
Section: Lack Of Clear Guidancementioning
confidence: 99%
“…Several studies have found that self-assessment empowers students to become owners of their learning (Azar & Tanggaraju, 2020;Luo et al, 2021;Mäenpää et al, 2020;Oh et al, 2021;Rini et al, 2020;Rizk, 2016;Wiliam & Leahy, 2020); other studies describe it as making learners co-owners of the learning process by having them critically reflect on their learning while addressing the needs of the learning task (Fletcher, 2016;Muñoz-Escalona et al, 2018). This process allows learners to review previous course content, assess their knowledge, and identify their weak points (Elkhatat et al, 2021), motivating them to learn actively (Styers et al, 2018) and influencing their self-regulated learning (Papanthymou & Darra, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they can be considered more versatile substitutes to lab experiments with limited specifications; and safer alternatives to operations that might include hazards [20,21]. Hence, a key component of engineering education is the integration of computer applications in order for students to acquire the skills and knowledge necessary to design, operate, maintain, and develop chemical processes in various industrial and environmental settings, as well as maintain academic integrity throughout the assessment process [10,11,13,12,14].…”
Section: Introductionmentioning
confidence: 99%